Izin Poligami di Pengadilan Agama (Suatu Tinjuan Filosofis) - Wati, Endang Rias; Hidayah, Siti; Aji, Yoga Purnama (CV. Kurnia Grup, 2025)
The regulations governing polygamy permits are made to maintain public order while providing legal protection for the rights and responsibilities of each individual in legal relationships. In addition, this regulation also aims to protect human rights as a whole. Therefore, the formal requirements in polygamy are designed so that the legal purposes of a marriage can be properly met. Philosophically, granting polygamy licenses not only helps achieve the goals of marriage, but also serves as a means of education for the public to better understand and obey the applicable law. Often, legal issues related to the creation of a child's birth certificate are the main reason for applying for a polygamy license. Although the application was not fully in accordance with the provisions of Article 4 paragraph 2 of the Marriage Law No. 1 of 1974, the panel of judges in some cases still granted permission, considering that the benefits obtained were greater than if they had to comply with strict marriage rules, especially in terms of the legalization of serial marriages and child welfare. This case also shows that religious court judges not only adhere to positive laws in Indonesia, but also consider the laws that live in society, including sharia and fiqh principles.